Simplification and electronisation of administrative procedure in the Visegrad Group countries - a sociological and legal approach - Rozczynski, Beniamin (Central European Public Administration Review, 2022)
Purpose: The purpose of the research was to examine the sociological issues related to the biographical experience of a participant in the ad - ministrative procedure in the Visegrad Group countries (the perception of public administration bodies and their organisation, current demands of the public in the field of public administration activities, providing ap - propriate tangible and intangible tools for officials) . The secondary goal of the research was to determine the nature, significance, consequences and form of comprehensive modernisation of existing simplifications of the administrative procedure (The author understands the concept of simplification of administrative procedure as “an administrative proce - dure separated from the general administrative procedure and charac - terized by simplification of general normative solutions”). Since the scope of the concept of ”electronisation of administrative procedure” does not fully include the concept of ”simplification of administrative procedure”, the research referred to two areas of the administrative procedure that are complementary to each other (the relationships that occur between them, including by specifying common and separate parts of electronisa - tion of administrative procedure, e.g. in the scope of keeping and making available files of procedure in electronic form). Moreover, solutions were presented in the field of simplification and electronisation of administra - tive procedures in the V4 Group countries, in institutional, subjective and objective terms. Design/Methodology/Approach: The analysis of domestic and foreign le - gal texts was used to implement the research assumptions (general legal regulation of administrative procedure presented by the Codes of Admin - istrative Procedure and COVID-19 regulations in the V4 Group countries). Empirical research using sociological research methods was conducted in connection with the analysis of currently applicable simplifying solu - tions the author implemented a component of social research using both qualitative methods – individual in-depth interviews with adult residents with biographical experience of being a participant in the administrative procedure (20 adults – 5 from each country of the V4 Group) as well as quantitative methods – online survey with participants of the administra - tive procedure (120 adults – 30 from each country of the V4 Group). In the research, the statistical method was applied to better illustrate the effectiveness of the currently conducted administrative procedure and to answer the hypotheses regarding the legitimacy of the development of the idea of administrative simplification. Findings: The analysis shows that it is not yet possible to speak of an ad - vanced development of administrative procedure in the Visegrad coun - tries. The delay of the public administration in applying solutions that simplify administrative procedure is mainly due to unclear regulations and significant financial outlays needed. The above state of affairs has a negative impact not only on entities participating in the procedure but also on public administration bodies and administrative courts. Practical Implications/Originality/Value: The initiated process of simpli - fying and electronising administrative procedure must always take the form of comprehensive legal solutions that will allow for effective and efficient operation of public administration bodies and enable individuals to exercise their fundamental rights. Therefore, the article presents the latest difficulties related to the administrative procedure and examples of their solution.
Keywords: digitalisation of public administration; digitalizacija javne uprave; dobra uprava; electronic communication; elektronsko komuniciranje; good administration; javna uprava v državah V4; načelo hitrosti postopka; new technologies; nove tehnologije; principle of speed of the proceedings; public administration in V4 countries